First evidence of bronze production in the Iron Age I southern Levant: A direct link to the Arabah copper polity - Tzilla Eshel; Yoav Bornstein; Gal Bermatov-Paz; Shay Bar (PLoS ONE, 2025)
This study presents new analytical data from the site of el-Ahwat, a short-lived Iron Age I settlement located at the northern edge of the Central Hill Country in Israel. The site’s substantial metal assemblage, including copper and bronze spills and slag, provides direct evidence for on-site bronze production. Microstructural features indicate that primary alloying of copper and tin—rather than the re-melting of scrap—was practiced at the site. Lead isotope analysis, chemical composition, and microstructure link some of the metal specifically to the Faynan ores, and other finds to the Timna ores, suggesting that both ores, possibly controlled by a joint polity, supplied copper to el-Ahwat. These findings challenge long-standing assumptions about the localization of bronzeworking in urban lowland centers, and open new perspectives on the inland trade routes and social organization of the early Iron Age southern Levant. We propose that el-Ahwat was part of a broader and more complex network of copper distribution and bronze production, extending from the Arabah to the coast, including also peripheral highland communities.